Hall itme motorunun sorgucundaki yük değişimi parçacıklarının incelenmesi - Çatmabacak, Önder (İstanbul Kültür Üniversitesi / Fen Bilimleri Enstitüsü / Fizik Anabilim Dalı, 2012)
Hall etkisi itme motorlarında, iç katottan gönderilen yüksüz yakıt anottan gönderilen elektronlarla çarpıştırılarak iyonlar elde edilir. Bu iyonların elektromanyetik alanda hızlandırılıp dışarı atılmasıyla da itme kuvveti elde edilir. Dışarı atılan bu iyonlar, elektronlar ve motordaki aşınmalarla kopan parçalarla beraber sorguç kısmını oluşturur. Sorguçta iyonlar motordan gelen birincil iyonlar ve bu iyonların sorguçtaki çarpışmalarından doğan ikincil iyonlar olmak üzere ikiye ayrılmaktadır. Ikincilleri oluşturan çarpışmalar arasında, motorun verimini etkilemesi bakımından en önemlisi yük değişimi çarpışmalarıdır. Yük değişimi iyonlarını incelemek için yapılan geçmiş çalışmalarda, çoğu simulasyon ve sayısal çalışmada reaksiyona giren parçacıkların çarpışma kesit alanlarına bakılmıştır. Yük değişimi parçacıklarını diğerlerinden ayırt etmek için yapılan diğer çalışmalarda ise çıkan iyonların akım yoğunluğu ve voltaj dağılımlarına bakılmıştır. Burada reaksiyonlardan çıkan iyonların iyonlaşma dereceleri ve kinetik enerjileri arasında ayırt edici bir oran bulunmuştur. Kültür üniversitesi fizik bölümü yüksek lisans bitirme tezi olarak yapılan bu çalışmada, yukarıda belirtilen ayırt edici iz belirlenen sorguç geometrisi üzerinde kullanılarak, Hall itme motorunun sorgucunda oluşan yük değişimi reaksiyonları hızları ve potansiyellerine göre incelenmiş ve sonuç olarak bu reaksiyonların sorguçtaki hörgüç yapısı ile ilişkisi ortaya konulmuştur.
Investigation of the charge-exchange particles on the Hall thruster's plume
On the Hall effect thrusters, propellant sent from the cathode to colliding with electrons comes from the anode on the inside of chamber. Ions are accelerated through the electric field and exhausted at the exit ( so called primary ions ) together with sputtered materials, electrons and neutrals. They all together form plume of thruster. Also the secondary ions are produced by different kind of collisions between the exhausted particles in the plume. One of these collisions is the charge exchange collision between the exhausted neutrals and primary ions between different charge states. Past studies have examined different features of the CEX reactions. Investigations are focused some parameters like cross-section area, density distribution and other plasma parameters to understanding the CEX reactions. Cross-section can be calculated according to the parameters to define features of the CEX reactions. Hereafter results were generally supported by simulations. When examining according to the cross-sectional areas of the reactions can not to be said efficient method due to the requires much more mathematical processes and man cross-section for CEX reaction are not available within the scientific literature. It does not provide any information about occurrence of the CEX reactions, structure of the hump and relation between them. Density distributions are measured in experiments, simulations presents no different perspective from the experiments. This studies has been directed to more experiment. Another investigations are focused on energy, potential and current density distribution. Studies show us that referring to ion energy distribution, some ions have more energy than others. In this case spectroscopic analysis were evaluated to identify characteristics of ions. Different probes used to measure ion velocities, masses and energies. From there ionization degree of the ions can be detected with known ion velocity and masses. However a relation can be described between ion mass and energy. Because ions with more positive charge must be lighter than others and storage more kinetic energy through the electric field cause of ionization degree. Recalling to the potential energy stored in electric field is transferred into ions as a kinetic energy, setup a relation between charge state and ion kinetic energy. Measured voltage distribution of this ions were found to have higher values in the possible reactions. This is expectable result cause of the definition of the CEX reaction. Referring to this definition energy and momentum are conserved and only transfer is electron trading during reaction. However, experimental results of the near of the exit are not reliable due to the precision of the probe measurements are affected by fluctuations at the thruster exit. Therefore we have less information about this region. According to this method is described in Ref. 1, we made a suitable analytic model consistent with experimental results for the region not available to measure. We predicting characteristics of the reactions in very-near field and showed that relation between CEX reactions and hump. However, experimental results of the near of the exit are not reliable due to the precision of the probe measurements are affected by fluctuations at the thruster exit. Therefore we have less information about this region.
Keywords: Astronomi ve Uzay Bilimleri; Astronomy and Space Sciences; Fizik ve Fizik Mühendisliği; Physics and Physics Engineering; Hall etkisi; Hall effect; Uzay araçları; Spacecrafts; İtme kuvveti; Thrust